EFFECTIVENESS OF INTERNATIONAL HEALTH REGULATIONS IN PREVENTION AND CONTROL OF EMERGENCY SITUATIONS OF SANITARY-EPIDEMIOLOGICAL AND BIOLOGICAL CHARACTER - A. Yu. Popova; V. P. Toporkov; V. Yu. Smolensky; N. D. Pakskina; S. K. Udovichenko; I. G. Karnaukhov; A. E. Shiyanova; S. A. Shcherbakova; V. V. Kutyrev (Проблемы особо опасных инфекций, 2017)
The paper describes the International Health Regulations (2005), hereinafter referred as IHR (2005), by the example of SARS, A/H5N1/, A/H1N1/09, Zika fever, and MERS-CoV control as an effective tool for prevention and control of public health emergences (ES of sanitary-epidemiological character) of international concern. Late detection of Ebola fever epidemic in West Africa (2013–2016) and announcement of public health emergency of international concern at the time when epidemic up-scaled to a threat to national security of the affected countries and high-priority threat to global community (ES of biological character) is attributed to non-use of methodological capacities of IHR (2005) on verification of ES at an early stage of epidemic development because of unpreparedness of local, regional, national and international public health services to such an epidemic situation. WHO plans to achieve scientifically-based reduction of the time from the onset of epidemic events to the effective response measures. Russian Federation, scientifically implementing IHR (2005) from the very beginning and having devised methodology of IHR implementation on the national level, has a strong premise for scientific provision of this process.